1998
DOI: 10.1021/ma971075z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Orientation at Rubbed Polyimide Surfaces Determined with X-ray Absorption Spectroscopy:  Relevance for Liquid Crystal Alignment

Abstract: The molecular orientation at the surface of polyimide (PI) alignment layers used for liquid crystal displays has been determined using X-ray absorption spectroscopy (NEXAFS). The second moments of the orientation distribution function obtained from a detailed analysis reveal that, upon rubbing, the PI substrates develop biaxiality and an inclination of a few degrees. For a nematic liquid crystal (LC) in contact with these alignment layers, the pretilt angle was determined and revealed a weak correlation with b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
71
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 37 publications
6
71
0
Order By: Relevance
“…All of them showed the same asymmetries with a larger p intensity along y than x and a larger intensity for negative than positive values of u . This asymmetry is also consistent with measurements on polyimides by others [16,18]. In contrast, for polystyrene the p intensity is larger along x than y and it is larger for positive than negative values of u.…”
Section: Molecular Reorientation By Rubbingsupporting
confidence: 92%
See 3 more Smart Citations
“…All of them showed the same asymmetries with a larger p intensity along y than x and a larger intensity for negative than positive values of u . This asymmetry is also consistent with measurements on polyimides by others [16,18]. In contrast, for polystyrene the p intensity is larger along x than y and it is larger for positive than negative values of u.…”
Section: Molecular Reorientation By Rubbingsupporting
confidence: 92%
“…These studies also showed the preferential near-surface alignment of polyimide chain segments along the rubbing direction [17] and the decay of the alignment from the surface toward the bulk of the film. NEXAFS studies also gave clear evidence for a preferential outof-plane tilt of phenyl rings at polyimide surfaces [15,16,18,19]. This tilt was linked with the pretilt angle of the LC on the surface.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…Although X-ray diffraction techniques have been used extensively as a structural probe, they are not particularly sensitive to these interfaces. Near-edge X-ray absorption fine-structure spectroscopy (NEXAFS), on the other hand, is sensitive to surface orientation and has been applied to investigate polymer structures, for example, in polyimide, [1] polyfluorene, [2] and polythiophene.[3] Here we show that NEXAFS band shapes and intensities are in fact also sensitive to the intermolecular p-interaction in regioregular poly(3-hexylthiophene) (rreg-P3HT) films. NEXAFS spectra of the same material deposited from different solvents and processing conditions are substantially different.…”
mentioning
confidence: 99%